2010
DOI: 10.1007/s00018-010-0328-4
|View full text |Cite
|
Sign up to set email alerts
|

PPARδ inhibits IL-1β-stimulated proliferation and migration of vascular smooth muscle cells via up-regulation of IL-1Ra

Abstract: Activation of peroxisome proliferator-activated receptor (PPAR) delta by GW501516, a specific PPARdelta ligand, significantly inhibited interleukin (IL)-1beta-induced proliferation and migration of vascular smooth muscle cells (VSMCs). This effect of GW501516 was dependent on transforming growth factor-beta, and was mediated through the up-regulation of IL-1 receptor antagonist. The inhibitory effect of GW501516 on VSMC proliferation was associated with cell cycle arrest at the G1 to S phase transition, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
33
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 59 publications
5
33
1
Order By: Relevance
“…Taken together, these data strongly suggest that the decrease in macrophage viability after TG treatment was due to activation of the apoptotic pathway. IL-1β is a cytokine produced by activated macrophages and plays a key role during inflammatory reactions, cell proliferation/differentiation, and apoptosis in atherosclerosis (28)(29)(30). Interestingly, we found a gradual decrease in IL-1β expression in a TG dose-dependent manner ( Fig.…”
Section: Tg Downregulates Il-1β Expressionmentioning
confidence: 63%
“…Taken together, these data strongly suggest that the decrease in macrophage viability after TG treatment was due to activation of the apoptotic pathway. IL-1β is a cytokine produced by activated macrophages and plays a key role during inflammatory reactions, cell proliferation/differentiation, and apoptosis in atherosclerosis (28)(29)(30). Interestingly, we found a gradual decrease in IL-1β expression in a TG dose-dependent manner ( Fig.…”
Section: Tg Downregulates Il-1β Expressionmentioning
confidence: 63%
“…In addition, both IL-1␤ and IL-18 have been shown to induce increased collagen production and proliferation of fibroblasts from various origins (12,16,33). Furthermore, studies have demonstrated that both cytokines can induce vascular smooth muscle proliferation and migration (6,23,54). Thus it is not unlikely that the lack of muscularization and fibrosis observed in ASC Ϫ/Ϫ mice is related to impaired IL-18 and IL-1␤ production.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies demonstrated that IL-1␤ increases the expression of cell adhesion molecules (295), MCP-1 (156), and lipocalin-2 (30) in vascular SMCs. In addition, it stimulates the migration (299) and proliferation of these cells (128,234). In the ApoE/IL-1␤ double knockout mouse model, IL-1␤ deficiency decreases the severity of atherosclerosis (121,134), further supporting the important role of IL-1␤ in vascular disorders.…”
Section: Adipokines With a Tight Link To Cardiovascular Diseasementioning
confidence: 94%